Maternal oxidative stress throughout pregnancy and early childhood neurodevelopment at different stages: insights from a prospective cohort study - Sen He; Jingyu Wang; Shuting Cao; Aizhen Wang; Yuyan Wang; Pei Li; Xiuli Cao; Rongrong Cheng; Ruixin Chen; Yin Wang; Fei Yang; Yuehao Fu; et al. (BMC Medicine)
Abstract Background Maternal oxidative stress during pregnancy plays a role as a hazardous factor of offspring neurodevelopment in animal models. However, epidemiological evidence remains limited. In this prospective cohort, we aimed to investigate the associations between maternal oxidative stress biomarkers (OSBs) across pregnancy and neurodevelopmental outcomes in different stages across early childhood. Methods This was a prospective cohort study conducted in 1791 mother–child pairs from Wuhan, China. Three OSBs, including DNA oxidative damage marker (8-hydroxy-2′-deoxyguanosine, 8-OHdG), RNA oxidative damage marker (8-hydroxyguanosine, 8-OHG) and lipid oxidative damage marker (4-hydroxy nonenal mercapturic acid, HNE-MA), were measured in repeatedly collected urine samples in three trimesters across pregnancy. We followed children at age 2, age 3, and age 6 years. At age 2 years, the Bayley Scales of Infant Development of China Revision (BSID-CR) was employed to assess children’s mental and psychomotor development. Brain-derived neurotrophic factor (BDNF) levels were measured in children’s plasma at age 3 years. The Wechsler Preschool and Primary Scale—Fourth Edition (WPPSI-IV) was used to assess children’s intelligence quotients at ages 6 years. Generalized estimating equation models were applied to estimate the associations between OSBs and neurodevelopmental outcomes. Results Higher maternal HNE-MA levels in late pregnancy were associated with lower mental development index at age 2 years (β =  − 0.95, 95% confidence interval (CI): − 1.78, − 0.11). Elevated early pregnancy HNE-MA levels were associated with decreased BDNF levels at age 3 years (β =  − 0.07, 95% CI: − 0.13, − 0.01). Each one-unit increase in natural log-transformed concentrations of 8-OHdG and 8-OHG in mid pregnancy was associated with a decrease in full-scale intelligence quotient at age 6 years by 1.55 points (95% CI: − 2.84, − 0.26) and 1.89 points (95% CI: − 3.30, − 0.49), respectively. Conclusions This study suggested that higher levels of OSBs in each trimester of pregnancy might be a risk factor of consistently suboptimal neurodevelopment across early childhood. This finding provides new epidemiological data on the linkages of oxidative stress across pregnancy to child neurodevelopment and gives clues to the possible sensitive windows.